Reality in mathematics assessment – an analysis of task-reality concordance in Finnish and Swedish national assessments - Palm, Torulf; Burman, Lars (NOMAD Nordic Studies in Mathematics Education, 2004)
There are a number of possible purposes that can be served by the inclusion of applied tasks in school mathematics. However, the attainment of several of these purposes is likely to be dependent on the applied tasks closely emulating real life task situations. The study reported in this paper is an analysis of this relation between school tasks and problems encountered in real life beyond school that require the application of mathematics for their solutions. The analysis was made on national assessments in Finland and Sweden. The assessment tasks were analyzed in relation to a number of aspects of real life task situations that are a part of a framework for considerations of the quality of real life simulations in school mathematics. There were a substantial proportion of applied tasks in the assessments. The results of the analysis display a large difference between the aspects, in the proportion of tasks that simulate them with reasonable fidelity. There was also a marked difference between the assessments for the different courses in the two countries, in the proportions of tasks simulating the aspects well.